Eugenol improves high-fat diet/streptomycin-induced type 2 diabetes mellitus (T2DM) mice muscle dysfunction by alleviating inflammation and increasing muscle glucose uptake - Jiang, Yuge; Feng, Chuanxing; Shi, Yonghui; Kou, Xingran; Le, Guowei (Frontiers in Nutrition, 2022)
Eugenol has been used in dietary interventions for metabolic diseases such as diabetes and obesity. However, the protective effect of eugenol on muscle function in diabetes is unclear. In this study, a high-fat diet (HFD) with a streptozocin (STZ) injection induced type II diabetes mellitus in a mouse model. Oral eugenol lowered blood glucose and insulin resistance of HFD/STZ-treated mice. Eugenol reduced HFD/STZ-induced muscle inflammation and prevented muscle weakness and atrophy. Eugenol administration significantly increased GLUT4 translocation and AMPK phosphorylation in skeletal muscle, thereby enhancing glucose uptake. By silencing the transient receptor potential vanilloid channel 1 (TRPV1) gene in C2C12 myotube cells, eugenol was found to increase intracellular Ca2+ levels through TRPV1, which then activated calmodulin-dependent protein kinase-2 (CaMKK2) and affected AMPK protein phosphorylation. In conclusion, eugenol is a potential nutraceutical for preventing high-glucose-induced muscle impairments, which could be explained by its mediating effects on glucose absorption and inflammatory responses in the muscle.